'Shades of grey': a focus group study on diagnostic uncertainty among general practitioners using point-of-care ultrasound - Hans-Christian Myklestul; Holgeir Skjeie; Mette Brekke; Trygve Skonnord (Taylor & Francis Group, 2024)
Background Point-of-care ultrasound (POCUS) has long been a diagnostic tool in family medicine, although most Norwegian general practitioners (GPs) who use POCUS, scans infrequently. The broad scope of family medicine, the relatively low prevalence of illnesses and infrequent use of POCUS imply that GPs may experience diagnostic uncertainty regularly.Aim To explore how GPs perceived and managed diagnostic uncertainty when using POCUS.Design and setting A qualitative focus group study among Norwegian GPs using POCUS.Methods Four focus group discussions were conducted. Total number of participants were 21. The interview guide was piloted, the focus group discussions were audio-recorded and transcribed, and Systematic Text Condensation, a thematic cross-case analysis, was used to analyse the data.Results Diagnostic uncertainty using POCUS was considered as aligning to the general clinical uncertainties in family medicine, but there were also POCUS-specific uncertainties in clinical decision-making. We generated six themes: emotional, cognitive, and ethical uncertainty using POCUS, communicating uncertainty to patients, interaction with specialists when using POCUS, and coping strategies of participants. POCUS results were the only results the participants sometimes withheld when communicating with other specialists. POCUS itself stimulated a renewed interest in family medicine. Scanning enough patients was the recommended coping strategy.Conclusion POCUS-using GPs experienced diagnostic uncertainty when using POCUS that aligned with other diagnostic uncertainties they experienced in everyday practice. However, they did not treat the results like other findings, as the GPs at times withheld their POCUS findings when interacting with secondary care specialists. This requires further investigation.